Processing of Fish Floating Feed Formulation from Tofu Pulp Waste - Sarjani, Tri Mustika; Abdul L. Mawardi; Ekariana S. Pandia; Elfrida Elfrida; M. Ali Akbar (Universitas Mataram, 2025)
The lack of knowledge and skills among the community, particularly the Mekar Jaya group in Seruway village, has resulted in the limited utilization of tofu dregs waste, which is primarily used as supplementary livestock feed. In fact, tofu dregs still contain sufficient nutrients to be used as a formulation ingredient for making floating fish pellets. The Mekar Jaya group already possesses village assets such as fish breeding ponds and fish pellet production machines, but fish farmers are still purchasing fish pellets for their fish farming. This community service activity aims to train fish farmers to process tofu dregs waste into fish pellet formulations, as well as to conduct hands-on training in producing floating fish pellets using the fish pellet machine. The method applied in this community service activity involves a structured training approach. Overall, the results of the community service activity show positive achievements. The Mekar Jaya farmer group has demonstrated independence in preparing floating fish feed formulations. They have also shown innovation and creativity in making floating feed and have begun independently producing the floating fish feed they learned through this training. The impact can be seen in the increased enthusiasm and motivation of the farming group in participating in the training provided